Corporate Power in Civil Society. - Sciulli, David (NYU Press, 2001)
The corporate mega-mergers of the 1980s and 1990s raise many troubling questions for social scientists and legal scholars. Do corporate globalism and the new, streamlined corporation help or hinder the development of civil society? Does the new power that increasingly deregulated businesses wield undermine the rights of citizens, or is this threat being exaggerated? Who has the authority to get things done in a corporation's name and who can be held legally responsible for a corporation's misbehavior? What role, if any, should the courts play in strengthening the rights of individuals who chal.